Letter (copy) : International Solidarity Fund - Tewson, Vincent
030-0143-001 Secretary's. HVT/FC/EK/1366. 24th June, 1938. Mr. G. Stolz, International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS VIIe. Dear Mr. Stolz, INTERNATIONAL SOLIDARITY FUND. I thank you for your letter of the 23rd instant giving particulars of goods which have been sent to Spain between the 16th February and the 31st May and also for the report of the Spanish Committee in regard to their work. I shall be glad to receive any further information which Mr. Schevenels can give both in regard to Spain and with respect to relief work in China. Yours sincerely, Assistant Secretary. 292/946/30/143